DEMOKRASI DELIBERATIF HABERMAS DAN PROBLEMATIKA IDEOLOGI DI RUANG PUBLIK DIGITAL - Silfanus Jemadin; Ando Tahamin (IN VERITATE LUX, 2026)
The development of digital technology has significantly transformed public spaces and contemporary democratic practices. Social media and digital platforms provide new spaces for broader political participation, but at the same time pose serious challenges to deliberative democracy. This article aims to analyze the problems of ideology in digital public spaces and their implications for the quality of democratic deliberation. This researchuses a qualitative approach with a literature study method and critical discourse analysis of relevant academic literature. The results of the study show that ideological polarization, the echo chamber phenomenon, the emotionalization of political discourse, the spread of disinformation, and digital power imbalances have weakened the communicative rationality that is the foundation of deliberative democracy. The findings of this article emphasize the importance of strengthening digital literacy, public discourse ethics, and digital platform governance as efforts to maintain the quality of deliberative democracy in the digital era.